Geospatial Modeling for Agroecological-Economic Characterization for the development of agro-export crops, Piura hydrographic unit, Peru. - Rivas Meza, Niell Wilson (2024)
The study aimed to create a geospatial model to identify agroecologically and economically viable zones for the main agro-export crops in the Piura hydrographic unit. Utilizing a Geographic Information System (GIS) and considering the bio-physical requirements of the crops, the research sought to delineate areas with high aptitude from both agroecological and socio-economic perspectives. Following the FAO's agroecological zoning methodology, various layers of spatial information were overlaid to define areas with specific suitability levels. Data were collected and analyzed from governmental sources such as SENAMHI, the Ministry of Agriculture, and the Regional Government of Piura to identify zones most optimal for each crop, closely approximating reality. The process included developing a Cartographic Model using the ArcGIS Model Builder tool, simplifying the creation of agroecological and economic zoning for each crop. Ultimately, optimal zones for the cultivation of paprika pepper, lemon, mango, passion fruit, and grape were determined. Specific land allocations were established, including 21284.9 hectares for paprika pepper, 9501.9 hectares for lemon, 4868.3 hectares for mango, 16577.1 hectares for passion fruit, and 7450.9 hectares for grape. This comprehensive approach, combining GIS technology, the FAO methodology, and governmental data, resulted in a precise model facilitating strategic decisions in agro-export cultivation.